(7p+4)=(p-2)

Simple and best practice solution for (7p+4)=(p-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7p+4)=(p-2) equation:


Simplifying
(7p + 4) = (p + -2)

Reorder the terms:
(4 + 7p) = (p + -2)

Remove parenthesis around (4 + 7p)
4 + 7p = (p + -2)

Reorder the terms:
4 + 7p = (-2 + p)

Remove parenthesis around (-2 + p)
4 + 7p = -2 + p

Solving
4 + 7p = -2 + p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1p' to each side of the equation.
4 + 7p + -1p = -2 + p + -1p

Combine like terms: 7p + -1p = 6p
4 + 6p = -2 + p + -1p

Combine like terms: p + -1p = 0
4 + 6p = -2 + 0
4 + 6p = -2

Add '-4' to each side of the equation.
4 + -4 + 6p = -2 + -4

Combine like terms: 4 + -4 = 0
0 + 6p = -2 + -4
6p = -2 + -4

Combine like terms: -2 + -4 = -6
6p = -6

Divide each side by '6'.
p = -1

Simplifying
p = -1

See similar equations:

| 3r-4=24 | | 12x-15=12x-8 | | -z+13=11 | | 3/4-1/2=5/4 | | 2/3x-5.25 | | f-1(4)=3x-4/5 | | (x+7)(3x-2)(x-10)=0 | | 3(2x+5)=48 | | -2h+14=-4 | | 84+2x+118+90+2x+68= | | 4x^4+16x^3+3x^2-36x-27=0 | | 7a+3a=24 | | -0.5x+1.31=-0.7x+9.11 | | 3n+-7=-4 | | 4-2g=14 | | 6z^8/16z^7 | | 10X+12=48+14X | | 2lnx-3=3 | | x-37=13 | | 6a^2+14a+3=0 | | 10m-870=50 | | -5f+370=-75 | | 2/3x=5.25 | | 16=4x^2-6 | | 6x^2=150x | | -1/3-9 | | M-19=2(4m+1) | | 4(2x+3)+3x=133 | | 72=8p-688 | | 10x-3=3x+2 | | 9c+5c=20 | | -5x-4(2x-3)=-92 |

Equations solver categories